1994
DOI: 10.3758/bf03205300
|View full text |Cite
|
Sign up to set email alerts
|

How accurate is size and distance perception for very far terrestrial objects? Function and causality

Abstract: This study investigated absolute estimation of size and distance for natural and artificial objects at viewing distances of 1.1-15.3 km (Experiments 1 and 2) and 0.4-5.0 m (Experiment 3). The main results were that, regardless of distance range, size and distance estimates (S' and D') were related to objective size and distance (S and D), respectively, by a power function with an exponent of unity, but great individual differences in exponent were obtained for the far objects. The ratio S'ID' was reasonably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…Higashiyama and Kitano (1991) demonstrated that other conditions being equal, S′/D′ is larger for neutral targets than for familiar persons. Higashiyama and Shimono (1994) argued that S′/D′ is larger in a reduced condition of viewing than in a normal condition of viewing. All of these studies have indicated that size and distance judgments are not influenced uniformly by environmental and task variables.…”
Section: Sdihmentioning
confidence: 99%
See 1 more Smart Citation
“…Higashiyama and Kitano (1991) demonstrated that other conditions being equal, S′/D′ is larger for neutral targets than for familiar persons. Higashiyama and Shimono (1994) argued that S′/D′ is larger in a reduced condition of viewing than in a normal condition of viewing. All of these studies have indicated that size and distance judgments are not influenced uniformly by environmental and task variables.…”
Section: Sdihmentioning
confidence: 99%
“…Authors examining visual space perception (Baird & Wagner, 1991;Gogel, 1998;Hershenson, 1992), haptic space perception (Barac-Cikoja & Turvey, 1995), and space cognition (Hubbard, Kall, & Baird, 1989) have developed their arguments on the basis of Equation 6. However, several studies (Gogel, Wist, & Harker, 1963;Higashiyama & Kitano, 1991;Vogel & Teghtsoonian, 1972) have provided evidence that Equation 6 is too restrictive to describe the relations among S′, D′, and θ. Alternatively, a number of studies (Foley, 1967(Foley, , 1968Higashiyama & Shimono, 1994;Oyama, 1974) have assumed that S′/D′ is a power function of θ:…”
mentioning
confidence: 99%
“…However, substituting terms other than ()' for ()has been proposed. According to these possibilities, ()' equals K(}(see Gogel & Da Silva, 1987a), Ke» (Foley, 1967(Foley, , 1968Gogel, 1971;Oyama, 1974), or a(}+ b (Higashiyama & Shimono, 1994), where K, n, a, and b are constants whose values depend upon the conditions. In direct measurements of ()' it has been found (often using quite different procedures) that the size of ()' obtained can substantially exceed that of () (Higashiyama, 1992), can equal () (Gogel, 1982), or in some cases can be considerably less than ()(see Gogel & Eby, 1997).…”
Section: Primary and Secondary Processesmentioning
confidence: 99%
“…Reviews of the early literature do not in general support this idea (2) , and neither do recent experiments (3)(4) . Classical SDI also fails to explain most size illusions (5)(6)(7)(8) .…”
Section: Predicted Effects On Perceived Sizementioning
confidence: 92%
“…In this version, misperceptions of linear size may occur through misperceptions of angular size or of distance, or of both. There is currently little evidence as to whether perceptual SDI holds any better than classical SDI, and the existing evidence is weak (3) . It is, however, worth enquiring whether the theory could account for underwater size perception.…”
Section: Predicted Effects On Perceived Sizementioning
confidence: 99%